A half-bridge distributed static compensator with a DC-link filter capacitor of a reduced size LCL filter - Meng, Xiangjian; Fang, Jingyang (Frontiers in Energy Research, 2022)
Distributed static compensators (DSTATCOMs), composed of power converters and passive filters, have been extensively utilized in distribution systems to improve their power quality. For the selection of passive filters, LCL filters with smaller sizes and lower costs are increasingly being adopted to replace the conventional L filters. However, the filter components of LCL filters are normally designed for the application of grid-connected inverters, and therefore, these passive components can be further optimized when applied to the DSTATCOM, where the grid-injected current is mainly capacitive. In this study, the novel LCL-filtered half-bridge DSTATCOM topology is proposed, where the conventional filter capacitor of the LCL filter is replaced by the DC-link capacitors with relatively larger capacitances. As a consequence, the grid-side inductance can be dramatically reduced from the order of millihenry to several microhenries. Furthermore, the current stress of semiconductor switches can be decreased. In addition, the power flow analysis and filter design procedure are presented in this study. It is revealed that a constant DC-link voltage can always be maintained, and the voltage variation across each capacitor can be well regulated with properly designed filters and controllers. Experiments were carried out on a down-scaled laboratory prototype, and simulation and experimental results are presented to verify the effectiveness of the proposed DSTATCOM topology.